Impact of Ambulatory Setting for Workers’ Compensation Patients Undergoing One-Level Minimally Invasive Transforaminal Lumbar Interbody Fusion and Review of the Literature - Nie, James W.; Hartman, Timothy J.; Pawlowski, Hanna; Prabhu, Michael C.; Vanjani, Nisheka N.; Oyetayo, Omolabake O.; Singh, Kern (World neurosurgery, 2022)
To compare perioperative characteristics and patient-reported outcome measures (PROMs) in workers’ compensation (WC) patients undergoing minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF) in either the inpatient/outpatient setting. Patients with WC undergoing 1-level MIS-TLIF were included. Patients were separated into inpatient/outpatient groups and demographically propensity score matched. PROMs included visual analog scale (VAS) back/VAS leg/Oswestry Disability Index (ODI)/12-item Short Form Physical Composite Score (SF-12 PCS)/Patient-Reported Outcomes Measurement Information System Physical Function (PROMIS-PF) preoperatively and 6 weeks, 12 weeks, 6 months, and 1 year postoperatively. Results were compared preoperatively and postoperatively and between cohorts. Minimum clinically important difference (MCID) achievement was determined through comparison with values established in the literature. A total of 216 patients were included (184 inpatient). The inpatient cohort (IC) showed worse perioperative outcomes in multiple measures (P < 0.034; all). The IC improved in all PROMs (P < 0.038; all), besides ODI at 6 weeks, SF-12 PCS at 6 weeks/6 months/1 year, and PROMIS-PF at 6 weeks. The outpatient cohort (OC) improved in VAS back at all time points and VAS leg at 6 months (P < 0.033; all). Between cohorts, the OC showed better scores with VAS leg/ODI/SF-12 PCS/PROMIS-PF at multiple time points (P < 0.031; all). Most of the IC achieved MCID, aside from ODI, whereas the OC achieved MCID in SF-12 PCS. MCID achievement between cohorts was higher in the IC at PROMIS-PF at 1 year and VAS back overall (P < 0.034; all). Despite more comorbidities and worse perioperative measures, the IC showed improved PROMs from preoperative to ≥1 follow-up visit, whereas the OC had improvement with only VAS back and leg. The IC showed multiple MCID achievements, whereas the OC showed MCID in only SF-12 PCS. These findings may help guide a surgeon’s decision making between inpatient/outpatient lumbar surgery in the WC population.